Genetic characterisation of the North-West Indian populations: analysis of mitochondrial DNA control region variations - Gagandeep Singh; Srinivas Yellapu; Harkirat Singh Sandhu; Indu Sharma; Varun Sharma; A. J. S. Bhanwer (Annals of Human Biology, 2021)
Background Human mitochondrial DNA presents several interesting characteristics, making it a favourable tool in the field of molecular anthropology, medical genetics, population history, and forensic science. Aim The present study investigated the mitochondrial DNA (mtDNA) control region variations in diverse ethnic groups of North-West India for which population data is insufficient. Subjects and methods The complete mtDNA control regions of 197 unrelated (for up to three generations) healthy individuals belonging to different ethnic groups of North-West India were sequenced. The haplotype frequencies, haplogroup distribution, and pairwise FST values between the studied and other worldwide populations were generated to study patterns of variation in human mtDNA. Results The results ascertained high gene diversity (0.998) in the studied maternal lineages, identifying 166 distinct haplotypes, of which 158 were unique and characterised by 117 variable sites. Three haplogroups: M3, M30, and U7 were observed to be the most prevalent, and phylogeographically a total of 55.86% of sequences were characterised into South Asian, followed by West Eurasian (40.18%) and East Asian (3.96%), ancestry haplogroups. Pairwise genetic differentiation comparisons revealed maternal homogeneity in the studied groups. No population substructure was detected within the North-West Indian populations. Conclusion The results of this preliminary study will contribute to an existing database of mtDNA variations of the Indian population and facilitate prospective studies investigating population genetics and human diseases.